PENGEMBANGAN KEMAMPUAN E-LEARNING BERBASIS WEB KE DALAM M-LEARNING - Panji Wisnu Wirawan (Jurnal Masyarakat Informatika, 2011)
Today, the use of mobile devices to support day-to-day communications has become part of public life, including communication by using the Internet through wireless networks. This can broaden the utilization of Mobile Learning (M-Learning). M-Learning can intersect with a web-based E-Learning in terms of data utilization. This article discusses the development of E-Learning capabilities that can be used for M-Learning using E-learning architecture that already exist before. As a result, the architecture of the new E-Learning with the ability of M-Learning is constructed and the prototype based on the architecture is developed.